2013
DOI: 10.1371/journal.pone.0075835
|View full text |Cite|
|
Sign up to set email alerts
|

Phanta: A Non-Fluorescent Photochromic Acceptor for pcFRET

Abstract: We have developed an orange non-fluorescent photochromic protein (quantum yield, 0.003) we call Phanta that is useful as an acceptor in pcFRET applications. Phanta can be repeatedly inter-converted between the two absorbing states by alternate exposure to cyan and violet light. The absorption spectra of Phanta in one absorbing state shows excellent overlap with the emission spectra of a number of donor green fluorescent proteins including the commonly used EGFP. We show that the Phanta-EGFP FRET pair is suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In addition, it has been shown that stable or “superfolder” proteins, are also more tolerant to mutagenesis compared with their less stable counterparts, enabling further engineering outcomes that, in some cases, may not have been otherwise possible . In this regard, both eCGP123 and TGP have been used to generate a range of photoswitching and photochromic proteins, (Langan, et al ., 2014, in preparation). High solubility and efficient folding are desirable properties when the FP is used as a fusion partner to prevent non‐specific interactions and aggregation that may create artifacts of subcellular distribution .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that stable or “superfolder” proteins, are also more tolerant to mutagenesis compared with their less stable counterparts, enabling further engineering outcomes that, in some cases, may not have been otherwise possible . In this regard, both eCGP123 and TGP have been used to generate a range of photoswitching and photochromic proteins, (Langan, et al ., 2014, in preparation). High solubility and efficient folding are desirable properties when the FP is used as a fusion partner to prevent non‐specific interactions and aggregation that may create artifacts of subcellular distribution .…”
Section: Resultsmentioning
confidence: 99%
“…Since chromophore formation and fluorescence is dictated by the protein fold, which is encoded by the amino acid composition, even slight variations in the sequence can lead to dramatic changes in photophysical and biophysical characteristics . Discovery of naturally occurring FP variants in parallel with optimization through random or rational mutagenesis, has led to an enormous number of FP‐based proteins including a palette of colors, photochromic versions, photoswitchable FPs, split FP based molecular reporters, inherently fluorescent biosensors, and highly stable variants …”
Section: Introductionmentioning
confidence: 99%
“…GFP-like proteins are valuable tools used extensively in molecular cell biology research [ 1 5 ]. In these genetically encoded probes, a tripeptide sequence undergoes a series of post-translational modifications to form a chromophore shielded from bulk solvent within a characteristic 11-stranded β-barrel [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescent DsRed (Φ F , 0.70) was converted to the chromoprotein DsRed-NF (Φ F , <0.001) by introducing four amino acid substitutions [ 22 ]. Most recently Phanta, an orange weakly fluorescent photoswitching protein was reported to have utility as a photochromic FRET (pcFRET) acceptor for EGFP, thereby overcoming the requirement for expensive time-resolved fluorescence imaging instrumentation when using non-fluorescent acceptors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This vivid color is most likely due to strong absorption of light by the fluorescent protein in these bacteria. Subsequently, we further examined the identified colonies under blue light to screen the dark colonies in a way similar to a previously reported method1118. As a result, we identified two colonies that had a blue color in daylight but showed dark fluorescence under blue light.…”
Section: Resultsmentioning
confidence: 94%